Dermatological indications for the use of isotretinoin beyond acne. (3rd October 2018) - Forbat, Emily; Ali, Faisal R.; Al-Niaimi, Firas
Abstract: While the use of isotretinoin has revolutionized the treatment of acne vulgaris, isotretinoin is increasingly recognized as a useful therapeutic option for many other cutaneous conditions. We review the evidence underlying the use of isotretinoin for a variety of dermatological indications including hidradenitis suppurativa, sebaceous gland pathology, rosacea, scarring alopecia, cosmetic dermatology, and non-melanoma skin cancer prophylaxis amongst other uses, and thus consider alternative uses within dermatology practice. The studies found benefit of isotretinoin, however most trials lacked statistical power and in many cases the use was limited to case series. Isotretinoin, if used within the correct cohort with appropriate pretreatment counseling regarding side-effects, is a well-tolerated medication with potential as either an adjunctive treatment or a second-line agent in those recalcitrant cases unresponsive to first-line therapy.